The Aquacultur Business of Jelawat ( Leptobarbus Hoevanii) at the Cages In Ranah Kampar Sub-District, Kampar Regency of Riau Province - Taslim, Rafika; Ramli, M.; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research on the aquacultur of Jelawat fish (Leptobarbus hoevanii) in the cages held in February 2015 at the Ranah village and Kampar subdistrict Kampar Regency. This research was aimed to find out how much production costs, how large the contribution costs of seeds and feed costs to the total cost of production as well as how large the profits obtained from the cultivation Jelawat fish in the cages. Based on the results of the research the costs of production incurred amounting to Rp. 40.608.500, the average contribution to the total feed cost is 80.5% while seeds cost total contribution towards total cost was 9.99% and the average profit earned by farmers is Rp. 6.515.500/harves. Thus the business in the cages of Jelawat fish profitable and useful the continued.Keywords: Jelawat Fish, of production contribution, advantage